2022
DOI: 10.3126/ajms.v13i11.45246
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical application of insulin versus platelet rich plasma versus normal saline dressings in the healing of diabetic foot ulcers: A study from a tertiary care center in India

Abstract: Background: Diabetic foot ulcers (DFU) are one of the major complications of diabetes. Despite proper insulin treatment and a strict diabetic diet, 15% of diabetic population develop non-healing ulcers which leads to amputation of the lower limb. Wound dressings represent a part of the management of diabetic foot ulceration. Normal saline (0.9%) wound dressings have been a useful adjunct in the treatment of open wounds. Topical insulin dressing improves wound healing by regulating oxidative and inflammatory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The result reported that platelet-rich plasma is a promising agent for faster wound healing and a more significant reduction in the size of DFU compared to topical insulin and other conventional dressings. However, topical insulin dressing is more effective than conventional dressing [29]. K Ramarao et al stated that topical insulin dressing provided favorable outcomes in patients with DFU by significantly reducing wound area compared to normal saline dressing and positively reducing wound infection [30].…”
Section: Discussionmentioning
confidence: 99%
“…The result reported that platelet-rich plasma is a promising agent for faster wound healing and a more significant reduction in the size of DFU compared to topical insulin and other conventional dressings. However, topical insulin dressing is more effective than conventional dressing [29]. K Ramarao et al stated that topical insulin dressing provided favorable outcomes in patients with DFU by significantly reducing wound area compared to normal saline dressing and positively reducing wound infection [30].…”
Section: Discussionmentioning
confidence: 99%